Does firm size improve firm growth? Empirical evidence from an emerging economy - Bentzen Jan; Tung Le Thanh (Economics and Business Review, 2023)
This study aims to examine the relationship between firm size and firm growth in Vietnam. The literature does not in general give support to Gibrat’s law stating that the expected increase in firm size is proportionate to its initial size, or that firm growth rates are independent of firm size. The present study relies on a sample of 578 listed Vietnamese companies representing eight different industries and covering the period 2010 to 2020. The analysis reveals that growth in firm revenues does not give support to a hypothesis of independence of initial firm sizes. When the firm size is measured by total assets the opposite result appears, i.e. the Gibrat’s law is not rejected. When including also the age of the firms in the test methodology the conclusion will be that firm growth—measured by revenue or assets—in all cases will decrease with firm size.